Synthesis and characterization of chitosan : poly (ethylene glycol) hydrogels - Mayas, Singh (2013)
In this project, a series of semi interpenetrating network (semi IPN) hydrogels were synthesized by photopolymerization of chitosan with PEG diacrylate (PEGDA) of different molecular weights and different water contents. PEG diacrylate was first synthesized from PEG (poly (ethylene glycol)), and the product of the reaction was characterized by FTIR and NMR. Chitosan and PEG diacrylate were photo-crosslinked to form a semi IPN under UV radiation. The swelling ratio of the hydrogel was calculated and the morphology and pore size were studied using SEM (Scanning Electron Microscope). [1st Award]